1975
DOI: 10.1063/1.430967
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from a binary liquid mixture above its critical consolute point

Abstract: Light scattering measurements were performed on the binary liquid mixture carbon tetrachloride–perfluoromethylcyclohexane at its critical concentration and immediately above its critical consolute temperature. Measurements of time averaged intensities as a function of scattering angle and temperature distance from the critical consolute temperature, T−Tc, yielded the critical parameters γ = 1.220±0.018, ξ0 = 2.28±0.21 Å, and ν = 0.626±0.013. Here γ describes the temperature dependence of the susceptibility χ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 39 publications
2
16
0
Order By: Relevance
“…and should be suppressable to some extent by rotating the cell until the flares at these points of the cell become minimum. We found that the upturn of 1 (8) the cells when the flares were minimized. Figure 6 shows the difference between the scattered light intensities (corrected for the scattering volume by multiplying sin 8) of benzene placed in two arbitrarily chosen cells.…”
Section: Stray Lightmentioning
confidence: 94%
See 4 more Smart Citations
“…and should be suppressable to some extent by rotating the cell until the flares at these points of the cell become minimum. We found that the upturn of 1 (8) the cells when the flares were minimized. Figure 6 shows the difference between the scattered light intensities (corrected for the scattering volume by multiplying sin 8) of benzene placed in two arbitrarily chosen cells.…”
Section: Stray Lightmentioning
confidence: 94%
“…We found that the upturn of 1 (8) the cells when the flares were minimized. Figure 6 shows the difference between the scattered light intensities (corrected for the scattering volume by multiplying sin 8) of benzene placed in two arbitrarily chosen cells. This difference vanishes within deviations of ± 1% in the angular range 5-150°.…”
Section: Stray Lightmentioning
confidence: 94%
See 3 more Smart Citations